Pulutan : from the soldiers' kitchen - Cruz, Elmer D.; Rosales, Emerson R.; Tordesillas, Ellen T.; Chua, Yvonne T. (Manila, Philippine: Anvil Publishing, 2007)
Pulutan conveys many things Filipino. That is probably why there is no english word truly captures the concept of pulutan. Pulutan conjures camaraderie. A drinking session is the Filipino concepts of breaking bread. Pulutan is the bread .
Introduction -- All-Time Favorites -- Atbp. -- Fried Pulutan -- Goat's Meat -- Inihaw Delight -- Kinilaw -- Lamang Dagat -- Luto sa Gata -- Lasang Exotic -- Usapang Lechon -- Pulutang Sabaw -- Not the Usual Parts .
Keywords: PHILIPPINE RECIPES; FILIPINO CUISINE